2001
DOI: 10.1097/00004647-200106000-00002
|View full text |Cite
|
Sign up to set email alerts
|

Positron Emission Tomography Compartmental Models

Abstract: The current article presents theory for compartmental models used in positron emission tomography (PET). Both plasma input models and reference tissue input models are considered. General theory is derived and the systems are characterized in terms of their impulse response functions. The theory shows that the macro parameters of the system may be determined simply from the coefficients of the impulse response functions. These results are discussed in the context of radioligand binding studies. It is shown tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
388
0
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 433 publications
(391 citation statements)
references
References 24 publications
1
388
0
2
Order By: Relevance
“…These were an irreversible one-tissue model (M1T1K, i.e. one-tissue compartment with one kinetic rate constant), a reversible one-tissue model (M1T2K, one-tissue compartment with two kinetic rate constants), an irreversible twotissue model (M2T3K, two-tissue compartments with three kinetic rate constants), and a reversible two-tissue model (M2T4K, two-tissue compartments with four kinetic rate constants) [31]. Variants of these models with and without a blood volume (V b ) component were evaluated.…”
Section: Kinetic Analysismentioning
confidence: 99%
“…These were an irreversible one-tissue model (M1T1K, i.e. one-tissue compartment with one kinetic rate constant), a reversible one-tissue model (M1T2K, one-tissue compartment with two kinetic rate constants), an irreversible twotissue model (M2T3K, two-tissue compartments with three kinetic rate constants), and a reversible two-tissue model (M2T4K, two-tissue compartments with four kinetic rate constants) [31]. Variants of these models with and without a blood volume (V b ) component were evaluated.…”
Section: Kinetic Analysismentioning
confidence: 99%
“…Similarly, spectral analysis can also be used for the same purpose (Cunningham and Jones, 1993;Murase, 2003). Although it differs from compartmental modeling conceptually, it does not differ much technically, because in both cases, the solution for the tissue time activity curve (tTAC) consists of a linear combination of exponential functions and possibly a constant term, convolved with the input function (IF) (Gunn et al, 2001;Schmidt, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…In a previous study, it was demonstrated that this is the optimal plasma input model for [ 11 C](R)-PK11195 studies (Kropholler et al, 2005). The other plasma input model was a three-tissue compartment model with different compartments for specific and nonspecific binding (Gunn et al, 2001) and was used to generate tissue time-activity curves (TACs) for the Monte Carlo simulations. …”
mentioning
confidence: 99%